Correlation between Hand Grip Strength and Duration in Computer Operators. - Nair, Preety M.; Nambiar, Veena Kiran; Verma, Shaswat; Ravindra, Savita (Indian Journal of Physiotherapy & Occupational Therapy)
Background: Musculoskeletal disorders are the most common self-reported work related illness. Highly repetitive jobs with grasping of the hands, repetitive bending of the wrist, vibration and localized mechanical pressure are the contributing factors towards the occurrence of repetitive stress injury. Many users complain about wrist fatigue, discomfort or pain after typing. This study aims to find out whether long work duration affects the hand grip strength in computer operators affecting his performance in the long run. Objectives: 1. To determine the hand grip strength in computer operators. 2. To determine the duration of work in computer operators. 3. To see whether there is any relation between the hand grip strength and the work duration in computer operators. Methods: A cross sectional descriptive study was undertaken. 174 subjects consisting of 87 computer operators and 87 sex and age matched normal individuals were taken for the study. An informed consent was obtained from the subjects. The baseline parameters were taken. The hand grip strength for both the dominant and non-dominant hand was measured using a JAMAR dynamometer. The number of years of work was also recorded. Data analysis:• Student's t-test has been used to find the age, gender, height, weight, hand length and hand width distribution within and between the study and control group. • The comparison between the hand grip strength in computer operators and the control group was done using Students t-test. • Pearson correlation co-efficient to find the relationship between the hand grip strength with the number of years of work. Results: There was a significant negative correlation between the hand grip strength and 11- 15 years of work. A significant decrease was noted in the hand grip strength of the dominant side in the study group in comparison to the control group. Conclusion: It was concluded that after 10 years of work there was a decrease in the grip strength in both the hands which could be attributed to the microscopic tears in the soft tissues and articular wear and tear over the years due to repetitive work.